THE PLACE AND SIGNIFICANCE OF PROSE AND POETRY WORKS STUDIED IN PRIMARY GRADES (Academia Science Repository, 2023)
In this article, there are opinions about the role and importance of prose and poetic works studied in elementary grades. The specific features of the genres presented in reading lessons in primary grades are revealed.